HUBUNGAN TINGKAT KECEMASAN DENGAN KUALITAS TIDUR MAHASISWA DALAM PENYUSUNAN TUGAS AKHIR DI MASA PANDEMI COVID-19 DI AKADEMI KEPERAWATAN JUSTITIA - Maya Labari (Journal of Borneo Holistic Health, 2022)
Abstract Students who are organizing their final assignments face different mental problems such as anxiety and sleep quality problems. According to information from WHO, the most widely recognized mental problems with predominance are anxiety and sadness problems, where there are more than 200 million people (3.6% of the population) who experience the adverse effects of anxiety problems. The reason is to determine the relationship between the level of anxiety and the nature of student sleep in planning the last activity during the Coronavirus pandemic at Justitia Nursing Academy. This examination is a quantitative exploration with different reciprocal examination configurations using a cross sectional methodology. This testing strategy uses complete examination, where the number of tests is equivalent to the population. The showed that most of the 24 respondents experienced moderate anxiety up to 10 respondents (41.7%). From effect of concentrate on sleep quality, it shows that most of the respondents' sleep quality is not good, namely 11 respondents (45.8%). From the results after the Spearman connection test, it was obtained a large value of 0.000 which indicates that the relationship between anxiety levels and sleep quality is very important with Spearman's relationship of 0.788 which indicates that the connection is positive with a strong connection strength. Some students who completed their final assignments experienced moderate anxiety and poor sleep quality, with the Corona virus pandemic which caused limited space for development, and mental problems that became negative thoughts such as stress.